DEEP MIND MAPPING MODEL IMPLEMENTATION DEVELOP CHILD CREATIVITY - Lubis, Hernani (Faculty of Tarbiyah nad Teacher Training, 2023)
Children's creativity is a potential that must be developed through the educational process. This study aims to describe the implementation of the mind mapping model in developing children's creativity in akidah akhlak lessons. This study uses a qualitative approach with a descriptive study method. The background of this research is in SDN 068003. Observation techniques, interviews, and document studies are three research data acquisition techniques. Then, the data were analyzed using an interactive analysis model, through the steps of data collection, data sorting, data presentation, and drawing conclusions. The results of this study indicate that the application of the mind mapping model makes it easier for educators during the thematic learning process, because it stimulates students to develop their creativity based on the spirit of group learning. Likewise, there are obstacles in implementing the learning model, namely the low focus of students in group activities, difficulties for teachers to control student learning behavior, and some students like to disturb their friends.